Structural Characteristics of Colombian School of Reinforced Concrete Moment Frames With Masonry Infill (2017)
Assessment of the seismic vulnerability of the building stock of a region is a key issue for its seismic risk evaluation. Schools are an important building class as they gather a high number of people, they are important for the social development and they could be used as shelters after an emergency. This paper presents an assessment of the characteristics of 77 buildings from 28 schools of Medellín, Itagüí and Sabaneta (Colombia). Each building is a reinforced concrete frame with masonry infill. Analyzed parameters include the number of stories, building height, ground floor area, height and plan irregularity, presence of short columns, walls materials, columns and walls dimensions, soil type, designed lateral load, level of maintenance, year of construction and presence of damage or retrofit intervention. The analysis of the schools characteristics represents useful information that could be used for the estimation of the vulnerability of this building class, as well as for its seismic risk assessment.